2019
DOI: 10.1051/ps/2018028
|View full text |Cite
|
Sign up to set email alerts
|

On the law of homogeneous stable functionals

Abstract: Let A be the L q −functional of a stable Lévy process starting from one and killed when crossing zero. We observe that A can be represented as the independent quotient of two infinite products of renormalized Beta random variables. The proof relies on Markovian time change, the Lamperti transform, and an explicit computation on perpetuities of hypergeometric Lévy processes previously obtained by Kuznetsov and Pardo. This representation allows to retrieve several factorizations previously obtained by various au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(33 citation statements)
references
References 56 publications
1
32
0
Order By: Relevance
“…• When α → 0 ⇔ a → m, our main result shows immediately that where the convergence follows from (2.5) in [24]. This is again an extension of the case m = 1 where Z −a a d −→ Γ 1 as a → 0.…”
Section: 22supporting
confidence: 61%
See 2 more Smart Citations
“…• When α → 0 ⇔ a → m, our main result shows immediately that where the convergence follows from (2.5) in [24]. This is again an extension of the case m = 1 where Z −a a d −→ Γ 1 as a → 0.…”
Section: 22supporting
confidence: 61%
“…which is valid for every b ∈ (a, 1), it is not a subordination formula. As in Corollary 4 (a) of [24], it can also be shown that X m,β is a multiplicative factor of X m,α for every 0 < β < α < m.…”
Section: 31mentioning
confidence: 76%
See 1 more Smart Citation
“…Finally, if lim u→∞ u −β φ φ(u) < ∞ then we may choose β = β φ and apply the above argument to conclude that ν T φ is moment determinate. 22…”
Section: Lemma 43mentioning
confidence: 99%
“…The case of M = 2 was first treated in [55] and then studied in depth in [59] in the context of the Mellin transform of certain functionals of the stable Lévy process. We extended the theory to general M in [78].…”
Section: N = M −mentioning
confidence: 99%